Kano Model Study on Vitanas Pineapple Processed Product Packaging in Pemalang: Analysis of Consumer Satisfaction and Expectations - Alkhamdi, Aden Nuzuli Gita; Watemin, Watemin; Utami, Pujiati; Lumongga, Dumasari (Indonesian Journal of Advanced Research, 2025)
This study aims to analyze consumer satisfaction and expectations regarding the 180 ml Vitanas pineapple fruit juice drink product packaging using the Kano Model method. The research was conducted in Pemalang Regency from June to July 2025, involving 50 respondents selected thru accidental sampling. Data was collected thru questionnaires and analyzed by grouping packaging attributes into must-be, one-dimensional, attractive, indifferent, or reverse categories. The research results show that brand attributes fall into the must-be category, while practical packaging, attractiveness and product information (nutritional information, composition, production date, and others) fall into the one-dimensional category, which has a significant impact on consumer satisfaction. The yellow packaging color falls into the attractive category. This finding provides strategic recommendations for the development of Vitanas product packaging to enhance competitiveness and increase customer satisfaction.